TRAINING OF FUTURE SPECIAL TEACHERS-DEFECTOLOGISTS TO IMPROVE THEIR PROFESSIONAL ACTIVITIES (Journal of Namibian Studies : History Politics Culture, 2023)
This article discusses the problem of training future special teachers to improve their professional activities. The paper provides substantiation of the relevance of this problem in the modern conditions of the humanization of the educational system, when the issue of preparing future special teachers to work with psycho-physiologically challenged children experiencing learning difficulties is acute. The development and implementation of an efficient model of professional training of future special teachers- as an organizer of correction measures would solve the problem of rehabilitation, social adaptation of a student with developmental and behavioral disabilities; compensate for shortcomings and improve lag in general development. In other words, the measures ultimately are meant to prepare a child for a full, active life in society.The paper considers the essence of the concept of improving the professional activity of future teachers. The methodological foundations of the prerequisites and the main directions of the use of technological techniques and techniques that are integral elements of the model of professional training of future special teachers to improve professional activity are identified; the importance of the ideas of designing a system of training future teachers to improve professional activity is determined. The article highlights a system of indicators, the generalized elements of which are indicators of personal readiness of future special teachers to improve their professional activities and their indicators of professional readiness.It is obvious that the professional formation of the personality of young teachers during their university training includes not only mastering a certain set of knowledge, skills and abilities, but also their personal self-improvement and the formation of an active life position. It also includes the education of such important qualities as responsibility for the formation of subjects of education, sociability, tact, critical thinking, self-criticism, etc.It is concluded that the implementation of an effective scientifically-based model of professional training of future special teachers to improve their professional activities contributes to improving the quality of correctional and pedagogical assistance to children in inclusive education.